(untitled) (Cadernos de Sociomuseologia, 2022)
This thesis is based on observations about the development of the National Cultural Policy of the Republic of Kiribati, which was articulated by the National Museum of the country together with regional and international organizations. To this end, the research started from a theoretical discussion on the disputes for the cultural sector in local and global institutions, with an analytical work on documents and international norms within the scope of UNESCO, the Universal Declaration of Human Rights and the pacts associated with Economic, Social, Cultural, Civil and Political Rights. The insertion of the social role of museums in international norms was analyzed in documents from the Santiago Roundtable (1972), from the formation of the International Movement for a New Museology (MINOM), from practical experiences and from statements coming from different meetings in the international context, such as the Declaration of Salvador (2007) and the constitution of the Ibermuseums Program, which influenced the latest UNESCO Recommendation concerning the Protection and Promotion of Museums and Collections (2015). Social museology and sociomuseology were discussed based on Ibero-American experiences, observed mainly in Portugal and Brazil. Based on a broad understanding, that sociomuseology and public policies coincide in the exploration of problems and possible solutions at the present time, research was undertaken to design the National Cultural Policy of the Republic of Kiribati, which was developed using an ethnographic approach and participatory actions with agents involved in the cultural area in the country. Keywords: Museums, Social Museology, Sociomuseology, Cultural Rights, Cultural Policy, Kiribati.